
If $2 - {\cos ^2}\theta = 3\sin \theta \cos \theta \ne \cos \theta $ than find the value of $\cot \theta $
A. \[\dfrac{1}{2}\]
B. \[0\]
C. \[ - 1\]
D. \[2\]
Answer
483.3k+ views
Hint: Here we will proceed by converting the given equation in terms of \[\tan \] by using the formulae of trigonometric ratios and trigonometric identities. Then solve the obtained equation by grouping the common terms. Further convert tan to cot to get the required answer.
Complete step-by-step answer:
The equation is $2 - {\cos ^2}\theta = 3\sin \theta \cos \theta $.
Dividing both sides with ${\cos ^2}\theta $, we have
\[
\Rightarrow \dfrac{{2 - {{\cos }^2}\theta }}{{{{\cos }^2}\theta }} = \dfrac{{3\sin \theta \cos \theta }}{{{{\cos }^2}\theta }} \\
\Rightarrow \dfrac{2}{{{{\cos }^2}\theta }} - \dfrac{{{{\cos }^2}\theta }}{{{{\cos }^2}\theta }} = \dfrac{{3\sin \theta }}{{\cos \theta }} \\
\Rightarrow 2{\sec ^2}\theta - 1 = 3\tan \theta {\text{ }}\left[ {\because \dfrac{1}{{{{\cos }^2}\theta }} = {{\sec }^2}\theta ,\dfrac{{\sin \theta }}{{\cos \theta }} = \tan \theta } \right] \\
\]
We know that ${\sec ^2}\theta = {\tan ^2}\theta + 1$. By substituting this formula, we have
\[
\Rightarrow 2\left( {{{\tan }^2}\theta + 1} \right) - 1 = 3\tan \theta \\
\Rightarrow 2{\tan ^2}\theta + 2 - 1 = 3\tan \theta \\
\Rightarrow 2{\tan ^2}\theta - 3\tan \theta + 1 = 0 \\
\]
Splitting and grouping the common terms, we have
\[
\Rightarrow 2{\tan ^2}\theta - 2\tan \theta - \tan \theta + 1 = 0 \\
\Rightarrow 2\tan \theta \left( {\tan \theta - 1} \right) - 1\left( {\tan \theta - 1} \right) = 0 \\
\Rightarrow \left( {2\tan \theta - 1} \right)\left( {\tan \theta - 1} \right) = 0 \\
\therefore \tan \theta = \dfrac{1}{2},1 \\
\]
We know that \[\cot \theta = \dfrac{1}{{\tan \theta }}\]. So, we have
\[
\therefore \cot \theta = \dfrac{1}{{\tan \theta }} = \dfrac{1}{{\dfrac{1}{2}}} = 2 \\
{\text{ }}\cot \theta = \dfrac{1}{{\tan \theta }} = \dfrac{1}{1} = 1 \\
\]
Therefore, the values of \[\cot \theta \] are 1 and 2.
Thus, the correct answer is D. 2
So, the correct answer is “Option D”.
Note: Here we have used the formulae of trigonometric ratios of \[\dfrac{{\sin \theta }}{{\cos \theta }} = \tan \theta ,\dfrac{1}{{{{\cos }^2}\theta }} = {\sec ^2}\theta ,\dfrac{1}{{\tan \theta }} = \cot \theta \]. And the trigonometric identity \[{\sec ^2}\theta = 1 + {\tan ^2}\theta \] to solve the given problem.
Complete step-by-step answer:
The equation is $2 - {\cos ^2}\theta = 3\sin \theta \cos \theta $.
Dividing both sides with ${\cos ^2}\theta $, we have
\[
\Rightarrow \dfrac{{2 - {{\cos }^2}\theta }}{{{{\cos }^2}\theta }} = \dfrac{{3\sin \theta \cos \theta }}{{{{\cos }^2}\theta }} \\
\Rightarrow \dfrac{2}{{{{\cos }^2}\theta }} - \dfrac{{{{\cos }^2}\theta }}{{{{\cos }^2}\theta }} = \dfrac{{3\sin \theta }}{{\cos \theta }} \\
\Rightarrow 2{\sec ^2}\theta - 1 = 3\tan \theta {\text{ }}\left[ {\because \dfrac{1}{{{{\cos }^2}\theta }} = {{\sec }^2}\theta ,\dfrac{{\sin \theta }}{{\cos \theta }} = \tan \theta } \right] \\
\]
We know that ${\sec ^2}\theta = {\tan ^2}\theta + 1$. By substituting this formula, we have
\[
\Rightarrow 2\left( {{{\tan }^2}\theta + 1} \right) - 1 = 3\tan \theta \\
\Rightarrow 2{\tan ^2}\theta + 2 - 1 = 3\tan \theta \\
\Rightarrow 2{\tan ^2}\theta - 3\tan \theta + 1 = 0 \\
\]
Splitting and grouping the common terms, we have
\[
\Rightarrow 2{\tan ^2}\theta - 2\tan \theta - \tan \theta + 1 = 0 \\
\Rightarrow 2\tan \theta \left( {\tan \theta - 1} \right) - 1\left( {\tan \theta - 1} \right) = 0 \\
\Rightarrow \left( {2\tan \theta - 1} \right)\left( {\tan \theta - 1} \right) = 0 \\
\therefore \tan \theta = \dfrac{1}{2},1 \\
\]
We know that \[\cot \theta = \dfrac{1}{{\tan \theta }}\]. So, we have
\[
\therefore \cot \theta = \dfrac{1}{{\tan \theta }} = \dfrac{1}{{\dfrac{1}{2}}} = 2 \\
{\text{ }}\cot \theta = \dfrac{1}{{\tan \theta }} = \dfrac{1}{1} = 1 \\
\]
Therefore, the values of \[\cot \theta \] are 1 and 2.
Thus, the correct answer is D. 2
So, the correct answer is “Option D”.
Note: Here we have used the formulae of trigonometric ratios of \[\dfrac{{\sin \theta }}{{\cos \theta }} = \tan \theta ,\dfrac{1}{{{{\cos }^2}\theta }} = {\sec ^2}\theta ,\dfrac{1}{{\tan \theta }} = \cot \theta \]. And the trigonometric identity \[{\sec ^2}\theta = 1 + {\tan ^2}\theta \] to solve the given problem.
Recently Updated Pages
The correct geometry and hybridization for XeF4 are class 11 chemistry CBSE

Water softening by Clarks process uses ACalcium bicarbonate class 11 chemistry CBSE

With reference to graphite and diamond which of the class 11 chemistry CBSE

A certain household has consumed 250 units of energy class 11 physics CBSE

The lightest metal known is A beryllium B lithium C class 11 chemistry CBSE

What is the formula mass of the iodine molecule class 11 chemistry CBSE

Trending doubts
State the laws of reflection of light

One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE

Difference Between Prokaryotic Cells and Eukaryotic Cells

How do I convert ms to kmh Give an example class 11 physics CBSE

Describe the effects of the Second World War class 11 social science CBSE

Which of the following methods is suitable for preventing class 11 chemistry CBSE
